PERCEPTIONS OF TEACHERS OF THE YEAR INITIAL OF ALVARES MACHADO ON THE USE OF TEACHING SYSTEM APOSTILLED - Silva, Edimar Aparecido da; Ferrari Leite, Yoshie Ussami [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The article, part of the dissertation Teaching system apostilled: the perceptions of teachers of the year early elementary school Alvares Machado - SP examines the perceptions of teachers in the first years of elementary school, the Municipal School of Alvares Machado - SP, on the use of an Teaching System Apostilled (TSA) in the classroom. From a qualitative perspective, the research was established as a case study, and data collection was done through questionnaires given to thirty-six teachers and methodologically interpreted from content analysis. The results indicated that most teachers have a positive perception of the use of TSA. It is recommended that the municipal education policy makers, municipal councils, institutions forming, the school administrators and teachers, to strengthen the opportunities for discussion and debate to better define municipal policy, reflecting on public-private partnerships.
Keywords: Teaching System Apostilled; Perceptions of Teachers; Municipal Education Networks